What scenarios for the Euro-Mediterranean in 2030 in the wake of the Arab spring? - Ayadi R.; Sessa C. (Moving forward in the Euro-Mediterranean Research and Innovation partnership. The experience of the MIRA project, 2013)
In the aftermath of the Arab Spring events, the Southern Mediterranean region has reached a turning point in its history, presenting as many opportunities as challenges for the EU. In this MEDPRO Policy Paper, the authors explore various possible scenarios that could play out in EU-Mediterranean relations over the next two decades but find, lamentably, that the EU has set itself on a ‘business as usual’ course, leaving the region open to further polarization and the involvement of other external players.